Impacto y significado del proyecto pedagógico integrador de áreas II: educación física (2019)
The presentation of the reflective research article aims to identify the opinions of the students of the LEB who studied the subject of PPIIA-II related to physical edu- cation. It was also proposed to determine the impact and practical significance of this subject in the academic training based on the interpretation of student opinions measured in three basic aspects: the personal, academic and professional aspects of future graduates. The methodology of action corresponds to the design of des- criptive research, where the researchers analyzed and interpreted the information collected from the different qualitative techniques of information collection. In ad- dition, the interpretive approach was used, with which the results were interpreted and analyzed. In conclusion, it can be mentioned that the pedagogical and didactic procedures implemented in the subject of PPIIA-II are successful for professional training in the field of physical education although they should be improved accor- ding to the students’ concept.